2006
DOI: 10.1111/j.1365-2362.2006.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a), type 2 diabetes and vascular risk in coronary patients

Abstract: Lp(a) in diabetic coronary patients is low and not associated with the incidence of vascular events. Although measurement of Lp(a) provides useful information in nondiabetic coronary patients, it is of little value in coronary patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 54 publications
8
34
1
Order By: Relevance
“…Our study did not have the power to dissect this relationship fully, because some groups (AAA patients and controls) had low numbers of diabetics. This relationship, however, is consistent with a recent study of 587 CAD patients, which showed that type 2 diabetes patients within the cohort had significantly lower concentrations of Lp(a) than those without diabetes (42 ). The mechanism by which diabetes decreases Lp(a) is unknown, but merits further investigation.…”
Section: Discussionsupporting
confidence: 78%
“…Our study did not have the power to dissect this relationship fully, because some groups (AAA patients and controls) had low numbers of diabetics. This relationship, however, is consistent with a recent study of 587 CAD patients, which showed that type 2 diabetes patients within the cohort had significantly lower concentrations of Lp(a) than those without diabetes (42 ). The mechanism by which diabetes decreases Lp(a) is unknown, but merits further investigation.…”
Section: Discussionsupporting
confidence: 78%
“…Venous blood samples were collected after an overnight fast of 12 h before angiography was performed, and laboratory measurements were performed from fresh serum samples, as described previously [31]. The serum levels of triglycerides, total cholesterol, and high density lipoprotein (HDL) cholesterol were determined by using enzymatic hydrolysis and precipitation techniques (Triglycerides GPO-PAP, CHOD/PAP, QuantolipLDL, QuantolipHDL; Roche, Basel, Switzerland) on a Hitachi-Analyzer 717 or 911.…”
Section: Measurement Of Biochemical Variablesmentioning
confidence: 99%
“…Other factors are involved in the thrombofilic status associated to diabetes, like increased plasma level of XII, XI, and VIII coagulation factors (9), platelet hypersensitivity to collagen (10), an increased circulating pool of tissue factor (11), and sometimes also an increase in Lipoprotein (a) plasma level (12).…”
Section: It Is Well-known That Diabetes Changes the Thrombohaemorrhagmentioning
confidence: 99%